PENGARUH LEVERAGE, PROFITABILITAS, DAN MODAL KERJA TERHADAP CASH HOLDING PERUSAHAAN MANUFAKTUR - Kurnia, Kurnia; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of leverage, profitability, and net working capital on cash holding in manufacturing companies. The data used in this study are secondary data obtained from financial statements over the last five years (2019–2023). The sampling method used is purposive sampling, with criteria of companies consistently publishing financial reports during the observation period. The analytical method used is multiple linear regression analysis.The results show that leverage has a negative effect on cash holding, indicating that companies with higher debt levels tend to hold less cash. Profitability has a positive effect on cash holding, meaning that companies with higher profits tend to maintain larger cash reserves. Meanwhile, net working capital also has a positive effect on cash holding, reflecting the company's liquidity condition. This research contributes to financial management by providing insights into factors influencing corporate cash holding policies. The findings can be used by management and investors in decision-making related to financial strategy.